Glacially moulded landslide runout debris in the Scottish Highlands. (2nd October 2018) - Ballantyne, Colin K.
ABSTRACT: A tongue of hummocky terrain ∼1 km long and ∼400 m wide extends downslope from the source area of a rock-slope failure that formed the summit arête of Sgùrr nan Ceathreamhnan in the NW Highlands. The tongue descends from ∼810 m to ∼650 m, crosses a corrie obliquely and laps onto an opposing slope. Individual hummocks are circular to elongate, up to 6 m high and streamlined. A possible origin as recessional or ice-stagnation moraines is inconsistent with hummock morphology and the alignment of the hummock belt, and the streamlining of the hummocks is incompatible with the form of unmodified rock-avalanche runout hummocks. It is proposed that the tongue of hummocky terrain represents rock-slope failure during or after ice-sheet deglaciation, and subsequent modification of runout debris by subglacial erosion during the Loch Lomond Stade (∼12.9–11.7 ka). This interpretation implies (i) that the debris was deposited by an excess-runout rock avalanche; (ii) that the glacier that subsequently occupied the corrie was warm-based; (iii) that Lateglacial landslide runout debris was not invariably evacuated by Loch Lomond Stadial glaciers, as previously suggested; and (iv) that some features interpreted as hummocky moraines elsewhere may have a similar origin.